2017
DOI: 10.1038/s41598-017-05912-x
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking Paracrine TGFβ1 Signals during Myofibroblast Differentiation in 3D Collagen Networks

Abstract: TGFβ1 is a key regulator for induction of tissue remodeling after dermal wounding. We present a model of paracrine delivery of TGFβ1 for differentiation of dermal fibroblasts based on a fibrillar 3D collagen matrix and embedded TGFβ1 releasing microparticles. We found differentiation into myofibroblasts was achieved in a TGFβ1 dependent manner at much lower doses than systemic delivery. This effect is accounted to the slow and sustained TGFβ1 release mimicking paracrine cell signals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 32 publications
(56 reference statements)
3
18
0
Order By: Relevance
“…Interestingly, we found that a low concentration of TGF-β1 (300 pg/mL) in the co-culture is needed to trigger myofibroblast differentiation, when compared to the systematic addition of 10 ng/mL TGF-β1. This result is in line with the previous report where slow and sustained TGF-β1 release in a picogram range from polyethylene glycol (PEG) microbeads embedded in 3D collagen matrix could fully differentiate fibroblasts into myofibroblast [73]. We also demonstrated that fibril density could influence myofibroblast differentiation as shown by matrix dependent expression of aSMA and matrix protein secretion (Coll1a1 and EDA-FN) in mono-culture and in co-culture with M -IL-4/-IL-13 .…”
Section: Il-4/il-13 Triggers Fibroblast Differentiation Into Myofibsupporting
confidence: 93%
“…Interestingly, we found that a low concentration of TGF-β1 (300 pg/mL) in the co-culture is needed to trigger myofibroblast differentiation, when compared to the systematic addition of 10 ng/mL TGF-β1. This result is in line with the previous report where slow and sustained TGF-β1 release in a picogram range from polyethylene glycol (PEG) microbeads embedded in 3D collagen matrix could fully differentiate fibroblasts into myofibroblast [73]. We also demonstrated that fibril density could influence myofibroblast differentiation as shown by matrix dependent expression of aSMA and matrix protein secretion (Coll1a1 and EDA-FN) in mono-culture and in co-culture with M -IL-4/-IL-13 .…”
Section: Il-4/il-13 Triggers Fibroblast Differentiation Into Myofibsupporting
confidence: 93%
“…Depending on the scientific question, various cell characteristics can be further analyzed manually or using an external analysis software from the obtained single cell trajectories including genealogies of dividing cells 36 , and cell behavior in complex bioengineered 3D systems e.g. biomimetic matrices with defined biophysical properties 8 or functionalized with other ECM components 39 , 40 , short-range cytokine gradients 38 , 41 and tissue boundaries 9 allowing for a better understanding of cell-cell-interactions and mimicking in vivo like microenvironments.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor cells invaded as groups of cells and were led by ASCs that stained positive for the myofibroblast marker α‐smooth muscle actin (α‐SMA). [ 15,31,35 ] Interestingly, co‐culture spheroids in which tumor cells were intermixed with ASCs isolated from human breast adipose tissue similarly promoted invasion (Figure 1f) suggesting that our data are of potential relevance to humans. Collectively, these data indicate that ASCs promote collective invasion of premalignant tumor cells via direct cell‐cell contact rather than secreted factors alone, and that myofibroblasts play a role in this process.…”
Section: Resultsmentioning
confidence: 76%
“…For example, cancer‐associated fibroblasts and thus, possibly obesity‐associated ASCs can promote tumor invasion via altered fibronectin deposition [ 12 ] and secretion of cytokines (including SDF‐1 and TGF‐ b 1). [ 31,34 ] Accordingly, our previous work suggests that obesity stimulates fibronectin deposition by ASCs [ 7 ] and that activated ASCs increase the secretion of factors contributing to elevated tumor malignancy. [ 40,43 ] Although secreted factors alone were not sufficient to promote extensive invasion in our experiments, cytokines can be sequestered within the ECM (e.g., due to differential binding to fibronectin).…”
Section: Discussionmentioning
confidence: 99%